Effect of electrical and chemical stimulation of the subthalamic nucleus on the release of striatal dopamine - Pazo, Jorge Horacio (2010)
High-frequency stimulation (HFS) of the subthalamic nucleus (STN) alleviates the cardinal symptoms of Parkinson’s disease, but the mechanisms underlying these clinical results remain to be clarified. The HFS of STN is associated with the release of dopamine (DA) in the striatum. This study examines possible mechanisms by which HFS–STN release DA. The experiments were performed in rats anesthetized with urethane. The STN was stimulated by electrical HF and chemical microinjections of an antagonist and an agonist of GABAA receptors, the bicuculline, and the muscimol, respectively. The extracellular striatal DA-DOPAC (3-4-dihydroxyphenilacetic acid) content was collected by means of intracerebral microdialysis cannula and analyzed with HPLC with an electrochemical detector. The HFS of STN and microinjection of bicuculline intrasubthalamic produced a significant increase of extracellular striatal DA, whereas DOPAC levels were unchanged. The microinjection of muscimol depresses spontaneous release of DA, without changes in DOPAC. The kainic acid lesion of the globus pallidus (GP) and the substantia nigra pars reticulata (SNr), ipsilateral to dialyzed striatum, did not modify the release of DA-DOPAC. These data provide evidence that the STN has a tonic action on the substantia nigra pars compacta (SNc), and the release of striatal DA by HFS–STN may be due to activation of the STN acting directly on SNc neurons.